FAKTOR-FAKTOR YANG MEMPENGARUHI RISK DISCLOSURE SEKTOR PERBANKAN YANG TERDAFTAR DI BEI - Keziah Karfinto, Rousilita Suhendah (Jurnal Paradigma Akuntansi, 2020)
The objective of this research is to obtain empirical evidence about the effect of firm size, leverage, profitability, and public ownership on risk disclosure in banking companies listed on the Indonesia Stock Exchange from 2016 to 2018. The research used 36 banking companies that were selected using purposive sampling method for a total of 108 data in three years. Data processed with EViews version 9. Random Effect Model is used to test the hypothesis in this study with panel data. The results of this research shows firm size has positive effect on risk disclosure, meanwhile leverage, profitability, and public ownership have no effect on risk disclosure.